The Effect of Fast Feet Exercises on Students’ Agility in Badminton Extracurricular Activities at SMAN 18 Garut - Ardiansyah, Agung Vicky; Arifin, Z.; Sonjaya, Azhar Ramadhana; Kosasih, Alam Hadi (JUMORA: Jurnal Moderasi Olahraga, 2025)
Agility is an important fitness component in badminton because it determines a player's ability to change direction quickly and accurately. However, initial observations of extracurricular badminton participants at SMAN 18 Garut show that students' agility is still low, as indicated by slow responses and position changes during training. This study aimed to determine the effect of Fast Feet Exercises on improving agility among students participating in the badminton extracurricular program at SMAN 18 Garut. The research used a quasi-experimental design with a One-Group Pretest–Posttest approach. Twenty students were selected using total sampling and participated in an intervention program for six weeks (three sessions per week, 45–60 minutes per session). The Illinois Agility Test was used to assess agility before and after the intervention. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Paired Samples t-test. The results showed a significant improvement in agility after the training program, as indicated by the decrease in average completion time from 20.1 ± 1.41 seconds to 17.85 ± 0.77 seconds (t = 8.309; p < 0.05). This finding demonstrates that Fast Feet Exercises effectively enhance agility by improving neuromuscular coordination, foot speed, balance, and movement efficiency. The program also resulted in more consistent performance among participants, as reflected by the reduced standard deviation. In conclusion, Fast Feet Exercises are proven to be an effective and practical method to improve agility in school-aged athletes, particularly those engaged in sports requiring rapid directional changes, such as badminton. Future studies are recommended to include control groups and investigate the long-term effects of this training method